The relation between the excised thyroid gland weight and postoperative complications in total thyroidectomy patients (Annals of Medical Research, 2021)
Aim: The purpose of this study was to determine the postoperative complications in total thyroidectomy patients based on the weight of the thyroid gland with retrospective screening.Material and Methods: A total of 263 adult patients, who underwent total thyroidectomy were included. The data automation system of the hospital and the files of the patients were examined retrospectively.Results: The total complication incidence was 24.3%, and these were determined as hypocalcemia, vocal cord paralyses (VCP), and hemorrhage and seroma at the surgery area. The rate of temporary hypocalcemia and permanent hypocalcemia rate was 20.1% and 1.5% respectively. The temporary VCP rate was 0.3% (n=1), and no permanent VCP was observed in the patients. The median thyroid weight was measured as 50 gr in patients without postoperative hypocalcemia, and as 40 g in the patients with hypocalcemia (p=0.283). There was no significant relation between the variability in the weight of the thyroid and postoperative hypocalcemia. However, the cervical lymph node dissection (LND) (p=0.006) and cervical dissection site (p=0.031) were significant in terms of postoperative complication development. In the multivariate analyses, it was found that female gender and LND were independent risk factors in the development of postoperative complications.Conclusion: It was determined that cervical LND and female gender were independent risk factors. Consistent with the literature findings, no significant results were found in the risk factors like heavy thyroid gland, presence of thyroid operation history, malignant thyroid pathology, retrosternal localization of the thyroid tissue, and hyperthyroidism.Keywords: Complications; hypocalcemia; thyroid weight; total thyroidectomy.